Pengembangan Media Gambar Alga Mikroskopis Sebagai Penunjang Mata Kuliah Botani Tumbuhan Rendah - Sri Amintarti; Aulia Ajizah; Nurul Hidayati Utami (Program of Biology Education, Universitas Lambung Mangkurat, 2019)
Effort to improve students' understanding for microalgae in Botani Tumbuhan Rendah course was needed a media. A media help student especially in practice lesson. This media developed by research in various of microalgae around Lambung Mangkurat University. This study aims to describe the validity and legibility of media. This research refers to the 4D development model. The main subjects of the study were 2 experts to obtain validity data and for legibility test were 5 students of Biology Education department. Then data were analyzed descriptively. The results of the study show that the developed microalgae media obtained an average validity of 93.8% which included very valid criteria, and for eligibility test by students obtained an average of 92.2% which included very good criteria. So all those media which developed can be used.